Prognostic value of lymphovascular and perineural invasion in squamous cell carcinoma of the tongue - Colonia-García, Adriana [UNESP]; Salazar-Peláez, Lina María; Serna-Ortiz, Carlos Andrés; Álvarez-Sánchez, Luis Gonzalo; de Andrade, Cleverton Roberto [UNESP] (Elsevier, 2022)
Objective: The objective of this study was to investigate the association between survival rate and lymphovascular invasion (LVI) and perineural invasion (PNI) in the tumor invasive front (TIF) of squamous cell carcinoma of the tongue (TSCC). Study Design: Seventy patients with TSCC were included. The retrospective analysis included demographic, clinical, and histopathologic data. Tissue blocks containing the TIF were stained with anti-α-smooth muscle actin and anti-S100 to detect LVI and PNI, respectively. Overall survival (OS) and disease-specific survival (DSS) were assessed using Pearson's chi-square test, Kaplan-Meier method, and Cox regression. Results: LVI and PNI were detected in 61.4% and 78.6% of the TSCC samples at the TIF, respectively. LVI and PNI were present in 54.3% of the cases and were associated with advanced clinical stage, lymph node resection, metastatic nodes, and lower survival (P < .05). The 5-year OS and DSS rates were 44% and 52%, respectively. Multivariate analysis showed that primary tumors >3.0 cm (hazard ratio = 4.29; P = .004) and a concomitant presence of LVI and PNI at the TIF (hazard ratio = 4.0; P = .012) were independent predictors for worse DSS. Conclusion: LVI and PNI, identified by immunostaining at the TIF, are potential prognostic markers of TSCC.